Automatic ultrasound-MRI registration for neurosurgery using the 2D and 3D LC2 Metric - Fuerst, Bernhard; Wein, Wolfgang; Mueller, Markus; Navab, Nassir (Medical Image Analysis, 2014)
To enable image guided neurosurgery, the alignment of pre-interventional magnetic resonance imaging (MRI) and intra-operative ultrasound (US) is commonly required. We present two automatic image registration algorithms using the similarity measure Linear Correlation of Linear Combination (LC2) to align either freehand US slices or US volumes with MRI images. Both approaches allow an automatic and robust registration, while the three dimensional method yields a significantly improved percentage of optimally aligned registrations for randomly chosen clinically relevant initializations. This study presents a detailed description of the methodology and an extensive evaluation showing an accuracy of 2.51mm, precision of 0.85mm and capture range of 15mm (>95% convergence) using 14 clinical neurosurgical cases.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Image registration; Linear correlation of linear combination; Similarity measure